2017
DOI: 10.17219/acem/62663
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity – related changes in ADMA and vWF levels in patients with type 2 diabetes – a preliminary study

Abstract: Background. The activity and the role of methylarginine in diabetic patients are subject to continuous research. The mechanism through which diabetes or insulin resistance increases asymmetric dimethylarginine (ADMA) serum levels is not fully understood. Studies indicate increased ADMA serum levels in patients with hypertension, hypercholesterolemia and hyperhomocysteinemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Ring et al [153] reported that a 4-month Nordic walking training was not sufficient to improve vascular function (i.e., aortic pulse wave velocity, aortic augmentation index, arterial stiffness, and reflection index and systemic vascular resistance). In contrast, Fiodorenko-Dumas and colleagues reported a significant reduction in serum levels of von Willebrand factor-a useful marker for endothelial cell efficiency-after 6 weeks of Nordic walking training, likely suggesting a positive influence of such unconventional outdoor activity on vascular function [154]. When considering gym-based activities, Zumba fitness and mini-trampoline rebounding exercise emerged as the most investigated ones [142,144].…”
Section: Exercise As Therapy For Diabetes Mellitus: Unconventional Anmentioning
confidence: 99%
“…Ring et al [153] reported that a 4-month Nordic walking training was not sufficient to improve vascular function (i.e., aortic pulse wave velocity, aortic augmentation index, arterial stiffness, and reflection index and systemic vascular resistance). In contrast, Fiodorenko-Dumas and colleagues reported a significant reduction in serum levels of von Willebrand factor-a useful marker for endothelial cell efficiency-after 6 weeks of Nordic walking training, likely suggesting a positive influence of such unconventional outdoor activity on vascular function [154]. When considering gym-based activities, Zumba fitness and mini-trampoline rebounding exercise emerged as the most investigated ones [142,144].…”
Section: Exercise As Therapy For Diabetes Mellitus: Unconventional Anmentioning
confidence: 99%
“…The third part of this study was establishing changes in new water soluble uremic toxins: ADMA, SDMA and TMAO. ADMA is an inhibitor of NO synthase (NOS) and a key enzyme for NO production [52,53,54,55]. SDMA is indirectly inhibiting NOS [13,17,55].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand increase of ADMA leads to renin-angiotensin-aldosterone system (RAAS) activation [52], decrease in sodium excretion, and increase in blood pressure [53,59], and all these changes could be beneficial during exercise. There were several studies analyzing the influence of exercise on ADMA after few weeks of training in patients with cardiovascular diseases [53,54,55,56,57,62,63,64]. Most of them showed decrease in ADMA level after series of trainings [53,54,55,56,63,64].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations